2016
DOI: 10.3847/1538-3881/153/1/16
|View full text |Cite
|
Sign up to set email alerts
|

A Catalog of Calibrator Stars for Next-Generation Optical Interferometers

Abstract: Benchmark stars with known angular diameters are key to calibrating interferometric observations. With the advent of optical interferometry, there is a need for suitably bright, well-vetted calibrator stars over a large portion of the sky. We present a catalog of uniformly computed angular diameters for 1523 stars in the northern hemisphere brighter than V = 6 and with declinations −15• < δ < 82• . The median angular stellar diameter is 0.527 mas. The list has been carefully cleansed of all known binary and mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…We used the Calibrator stars for 200 m baseline interferometry by Mérand et al (2005, hereafter MER05, using the method: absolute spectro-photometric calibration) for 15 large (∼ 1 mas) K0III-K5III calibrators with a typical precision of the order of 1-2% on diameter and 1% in visibility calibration, the Catalogue of Calibrator Stars for LBSI by Bordé, P. et al (2002, using the same method) for one K1III star with a similar level of precision, and the JMMC Stellar Diameters Catalogue (JSDC, Bourges et al 2017, using the method: photometric calibration) for 65 smaller ( 0.5 mas) calibrators with a typical precision of 10-20% in diameter and 2% in visibility. Swihart et al (2017) have showed that the indirect spectro-photometric calibration method for large calibrators is not biased, as their catalogue is consistent both with interferometric measurements and catalogue by MER05. For most of our science stars (15 of 20) we observed small calibrators from JSDC or ones smaller than the target from MER05.…”
Section: Data Setsupporting
confidence: 55%
“…We used the Calibrator stars for 200 m baseline interferometry by Mérand et al (2005, hereafter MER05, using the method: absolute spectro-photometric calibration) for 15 large (∼ 1 mas) K0III-K5III calibrators with a typical precision of the order of 1-2% on diameter and 1% in visibility calibration, the Catalogue of Calibrator Stars for LBSI by Bordé, P. et al (2002, using the same method) for one K1III star with a similar level of precision, and the JMMC Stellar Diameters Catalogue (JSDC, Bourges et al 2017, using the method: photometric calibration) for 65 smaller ( 0.5 mas) calibrators with a typical precision of 10-20% in diameter and 2% in visibility. Swihart et al (2017) have showed that the indirect spectro-photometric calibration method for large calibrators is not biased, as their catalogue is consistent both with interferometric measurements and catalogue by MER05. For most of our science stars (15 of 20) we observed small calibrators from JSDC or ones smaller than the target from MER05.…”
Section: Data Setsupporting
confidence: 55%
“…The JSDC diameters are listed in Table 4 and are estimated by making a polynomial fit of the differential surface brightness of a star as a function of spectral type (Chelli et al 2016). The JSDC diameters are generally in good agreement with independent estimates from CADARS (Pasinetti Fracassini et al 2001) and Swihart et al (2017) (see Table 4). The exception is the calibrator for ζ Oph, HD 154445, which has a larger size in the JSDC Catalog.…”
Section: Observationsmentioning
confidence: 63%
“…The exception is the calibrator for ζ Oph, HD 154445, which has a larger size in the JSDC Catalog. The angular diameter of HD 154445 is given as 0.16 mas by CADARS, 0.18 mas by Swihart et al (2017), and a spectroscopic study by Lyubimkov et al (2002) implies a diameter of 0.21 mas. These diameter estimates are all significantly smaller than the JSDC value of 0.28 mas, so we adopted the angular diameter found by Swihart et al (2017) of 0.18 mas for this calibrator.…”
Section: Observationsmentioning
confidence: 99%
“…List of our program CBe stars and the log of observations. 𝑎 Zhang et al (2005); 𝑏 Stevens et al (2017); 𝑐 Gontcharov (2012); 𝑑 Chen et al (2016);𝑒 Varga et al (2018);𝑓 Swihart et al (2017) …”
mentioning
confidence: 99%